USP19 deficiency enhances T-cell-mediated antitumor immunity by promoting PD-L1 degradation in colorectal cancer - Feng Shi; Guang-Jing Li; Yi Liu; Hai-Meng Zhou; Yue Zhang; Si-Yi Wei; Bo-Jun Zan; Meng Gao; Fei-Shan Chen; Bo-Xin Li; Bai-Qi Wang; Ming-You Dong; et al. (Pharmacological Research)
Colorectal cancer (CRC) is characterized by a highly immunosuppressive tumor microenvironment, which limits the effectiveness of current immunotherapies. Identifying strategies to overcome this resistance is critical for improving treatment outcomes. In this study, we discovered that USP19 plays a pivotal role in regulating T-cell-mediated antitumor immunity through a CRISPR/Cas9 sgRNA library screen and co-culture assays with activated T cells. We demonstrated that USP19 deficiency significantly enhances the susceptibility to T cell-mediated cytotoxicity in CRC cells, organoids, and mouse models. Transcriptomic sequencing (RNA-seq) revealed activation of the PD-1 pathway in tumor with USP19-deficiency cells. Mechanistic investigations revealed that USP19 directly stabilizes PD-L1 by binding to its intracellular domain and preventing its degradation via K48-linked ubiquitination and proteasomal pathways. Clinically, USP19 expression was found to be significantly elevated in CRC tissues and was positively associated with PD-L1 levels, advanced tumor grade, poor differentiation, and TP53 mutations, highlighting its potential as a biomarker for aggressive CRC. Importantly, in vivo experiments demonstrated that targeting USP19, in combination with αPD-L1 therapy, synergistically suppressed CRC progression. This combination not only reduced PD-L1 levels but also enhanced CD8+ T-cell activation and GzmB infiltration, resulting in robust antitumor effects. These findings establish USP19 as a key driver of immune evasion in CRC and suggest that targeting USP19 could enhance the efficacy of immunotherapy, providing a promising new avenue for CRC treatment.